Irregular Modular Subarrayed Phased Array Tiling by Algorithm X and Differential Evolution Algorithm - Jiang, Hailing; Gong, Yu; Zhang, Junyi; Dun, Shubo (IEEE antennas and wireless propagation letters, 2023)
In this letter, an efficient and versatile method based on algorithm X and differential evolution algorithm is proposed to synthesize irregular modular subarrayed planar phased arrays with exact tiling. To alleviate the time-consuming problem of using algorithm X to synthesize large arrays, the proposed method obtains the subarray configuration with exact tiling through twice-partitioning operations. In the first partition process, the planar phased array is divided into several first-level subarrays. In the second partition process, the first-level subarrays are respectively divided into pre-specified irregular modular subarrays, called second-level subarrays. All feasible schemes for dividing the first-level subarrays and second-level subarrays can be obtained by algorithm X. Through the above partition process, the partitioning paradigm can be represented by only a few variables, which can be optimized by swarm intelligence algorithms. In this letter, the variables representing the subarray configuration are optimized by differential evolution algorithm to obtain excellent radiation performances. Three representative numerical examples are presented and discussed to assess the validity, efficiency, and reliability of the proposed method.